2023
DOI: 10.2514/1.a35401
|View full text |Cite
|
Sign up to set email alerts
|

Space Flight Demonstration of Rotating Detonation Engine Using Sounding Rocket S-520-31

Abstract: To create a new flyable detonation propulsion system, a detonation engine system (DES) that can be stowed in sounding rocket S-520-31 has been developed. This paper focused on the first flight demonstration in the space environment of a DES-integrated rotating detonation engine (RDE) using S-520-31. The flight result was compared with ground-test data to validate its performance. In the flight experiment, the stable combustion of the annulus RDE with a plug-shaped inner nozzle was observed by onboard digital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…It was also found that orbital transfer systems costs can be lowered by adopting PDCs [21,22], while the compact configuration of the engine makes it a suitable candidate for powering Unmanned (Combat) Aerial Vehicles [23] and rocket engines [19]. Currently, the advantages of pressuregain combustion propulsion systems are renewing interest in such engines, and interesting new developments in the field of detonation-based engines have been reported over the last year [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that orbital transfer systems costs can be lowered by adopting PDCs [21,22], while the compact configuration of the engine makes it a suitable candidate for powering Unmanned (Combat) Aerial Vehicles [23] and rocket engines [19]. Currently, the advantages of pressuregain combustion propulsion systems are renewing interest in such engines, and interesting new developments in the field of detonation-based engines have been reported over the last year [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, active research has been conducted on RDE over the past decade. In recent years, practical research and benefits have been reported [9][10][11][12] Research is being conducted to implement PGC, which is realized via detonative combustion. Wu et al [13] carried out thermodynamic cycle analyses and found that detonative combustion is not completely identical to the Humphrey cycle, but it generally has similar characteristics to the Humphrey cycle.…”
Section: Introductionmentioning
confidence: 99%
“…During this time, significant progress has been made in the research and development of rotating detonation engines [12][13][14][15] . A wide series of experimental investigations have explored various aspects of detonation-based propulsion systems including operability and performance [16][17][18][19] , injection response 4,20 , fundamental detonation structure [21][22][23][24] , effect of fuel and oxidizer compositions 25,26 , nozzle concepts 4,27 , system integration 28 , measurement techniques [29][30][31] and flight technology 32,33 . Although there is a large body of work characterizing various aspects of rotating detonation waves, there remains to be a coordinated effort to unify the results gathered under perfectly matching conditions for RDRE verification and validation.…”
mentioning
confidence: 99%